The Enhancement of Business Process Management and Financial Accountability in the MBG Program: A Qualitative Study Based on FGD Findings at SPPG in West Bandung Regency - Shanty Sriharyati; Budi Harto; Alia Gantina Shiti Mariam; Sulistianingsih; Sri Marhanah (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2025)
This study investigates the dynamics of financial accountability and business process management (BPM) in the MBG (Menu Bergizi Gratis) program at SPPG in Kabupaten Bandung Barat. In-depth conversations from a Focus Group Discussion (FGD) with a variety of stakeholders, including village authorities, SPPG managers, nutritionists, finance officers, educators, health officers, and community representatives, are used in this qualitative study. The results show how operational, logistical, and governance issues interact intricately to influence MBG service delivery performance. Inconsistent SOP adherence, delays in school distribution, varying raw material quality, a lack of human resources, especially in the area of nutrition knowledge, excessive food waste, and deficiencies in cross-agency cooperation are some of the main problems. Financial accountability difficulties also occur, especially involving insufficient paperwork, transactions missing formal receipts, and supplier reliability problems. The research also emphasizes the need for better traceability when events happen, community concerns about food safety, and burden-shifting impacts on teachers during distribution. Stakeholders show a strong commitment to enhancing service quality and preserving program continuity in spite of these obstacles. The study concludes that improved monitoring systems, consistent operational controls, integrated coordination, and a clearer division of roles among actors are all necessary to boost BPM. In the meantime, clear reporting, supplier verification, and organized documentation processes can enhance financial accountability. These observations have useful ramifications for improving MBG governance and guaranteeing long-term program execution at the local level.